Comparative analysis of innovative behavior in migrant workers and local employees in the Greater Bay Area of China - Wang, Lanxia; Wang, Yiyan; Liu, Shuaifang; Zhang, Hui; Wei, Na; Zhou, Bilei; Li, Jun (Justin) (Frontiers in Psychology, 2025)
IntroductionThe influx of foreign workers into Chinese cosmopolitan hubs has reshaped workplace dynamics, yet research on their innovation behaviors remains limited, particularly in the post-COVID-19 context. This study examines and compares the relationships between leader–member exchange (LMX), job autonomy, innovative work behavior, and job performance among foreign workers and local employees, addressing gaps in understanding how these factors influence organizational success during and after the pandemic.MethodsData were collected from 449 employees (295 foreign workers and 154 local employees) in China’s food and beverage (F&B) industry during the COVID-19 pandemic. A multiple group analysis approach was employed to test hypotheses and compare interrelationships between variables across the two groups. Structural equation modeling (SEM) was utilized to assess direct and indirect effects.ResultsLMX and job autonomy positively correlated with innovative work behavior and job performance for both groups. However, significant differences emerged: job autonomy had a stronger impact on innovative behaviors among foreign workers than local employees. No notable differences were found in LMX effects. These findings highlight the role of cultural and contextual factors in shaping autonomy’s influence on innovation.DiscussionThe study underscores the importance of fostering LMX and job autonomy to drive innovation and performance, particularly as organizations adapt to post-pandemic recovery. For multinational workforces, tailored strategies that address cultural differences in autonomy perception are critical. Practical implications include cultivating inclusive innovation cultures and leveraging autonomy to enhance foreign workers’ contributions. Future research should explore longitudinal impacts of workplace dynamics in diverse sectors.